PENGENDALIAN LANTAI PABRIK DENGAN LOAD ORIENTED MANUFACTURING CONTROL PADA INDUSTRI MEBEL (STUDI KASUS PT “X”) - Sri Hartini; Singgih Saptadi; Nurlaila Kadarina (Diponegoro University, 2009)
Load Oriented Manufacturing Control (LOMC) is an input-output control system development thatconsidered work load in every work center. Production planning starts with determining production leadtime, then work load control (WLC). WLC consist of defining criteria and determining release procedure tothe shop floor for items that will be processed. This research tried to implement LOMC concept in afurniture company called PT.X. The result of the research showed that LOMC could improve throughputand minimize work in process (WIP).